2017
DOI: 10.1002/bjs.10488
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of mesh fixation with glue or sutures for Lichtenstein hernia repair

Abstract: Atraumatic mesh fixation with glue was quicker and resulted in less acute postoperative pain than sutures for Lichtenstein hernia repair. Registration number: NCT02632097 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 33 publications
1
42
1
5
Order By: Relevance
“…Of 2682 articles identified by the literature search, 51 were selected for full‐text assessment and 29 articles met the inclusion criteria. After removing duplicate articles, 25 were included in the meta‐analysis, representing 23 studies ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 2682 articles identified by the literature search, 51 were selected for full‐text assessment and 29 articles met the inclusion criteria. After removing duplicate articles, 25 were included in the meta‐analysis, representing 23 studies ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…One study had a multiarm trial design comparing cyanoacrylate glue fixation and ProGrip™ self‐gripping mesh with suture fixation of the mesh. Five studies reported on fibrin glue fixation, eight on cyanoacrylate glue fixation and 11 on the use of ProGrip™ self‐gripping mesh. Of the 23 articles included in the meta‐analysis, 15 provided the incidence of chronic pain at 12 months, according to the definition provided in the methods.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations